Image Guidance for Ventricular Shunt Surgery: An Analysis of Hospital Charges. Issue 4 (1st May 2019) - Ajmera, Sonia; Motiwala, Mustafa; Khan, Nickalus R; Smith, Lydia J; Giles, Kim; Vaughn, Brandy; Klimo, Paul
Abstract: BACKGROUND: Image guidance for shunt surgery results in more accurate proximal catheter placement. However, reduction in shunt failure remains unclear in the literature. There have been no prior studies evaluating the cost effectiveness of neuronavigation for shunt surgery. OBJECTIVE: To perform a cost analysis using available hospital charges of hypothetical shunt surgery performed with/without electromagnetic neuronavigation (EMN). METHODS: Hospital charges were collected for physician fees, radiology, operating room (OR) time and supplies, postanesthesia care unit, hospitalization days, laboratory, and medications. Index shunt surgery charges (de novo or revision) were totaled and the difference calculated. This difference was compared with hospital charges for shunt revision surgery performed under 2 clinical scenarios: (1) same hospital stay as the index surgery; and (2) readmission through the emergency department. RESULTS: Costs for freehand de novo and revision shunt surgery were 23 946.22 and 23 359.22, respectively. For stealth-guided de novo and revision surgery, the costs were 33 646.94 and 33 059.94, a difference of 9700.72. The largest charge increase was due to additional OR time (34 min; 4794), followed by disposable EMN equipment (2672). Total effective charges to revise the shunt for scenarios 1 and 2 were 34 622.94 and 35 934.94, respectively. The cost ratios between the total revision charges for both scenarios and the difference in freehand vs EMN-assisted shunt surgery (9700.72) were 3.57 and 3.70, respectively. CONCLUSION: From an economic standpoint and within the limitations of our models, the number needed to prevent must be 4 or less for the use of neuronavigation to be considered cost effective.